Vibrotactile feedback during physical exercise: Perception of vibrotactile cues in cycling - Peeters, T.; van Breda, E.; Saeys, W.; Schaerlaken, E.; Vleugels, J.; Truijen, S.; Verwulgen, S. (International Journal of Sports Medicine, 2019)
The aim of this study was to investigate the perception of vibrotactile signals during physical exercise by comparing differences in recognition between stationary and cycling positions. The impact of physical exercise on the ability to perceive vibrotactile cues is unknown, whereas the recognition in stationary position has been shown previously. Vibrating elements were positioned at 3 locations on the thighs and spine of 9 athletes to apply various vibrotactile cues. Subjects performed at 0, 50, 70 and 90% of their maximal cycling power output and denoted the interpretation of the vibration signals on a touchscreen. The results show a similarity in correct recognition between stationary position and physical exercise for the thighs and spine (p>0.1) and demonstrate a decrease in response time for 70 and 90% levels of physical exercise compared to 0 and 50% (p<0.001). Furthermore, vibrotactile signals at the spine are noticed more accurately and more rapidly compared to the thighs (p<0.01). These results suggest that vibrotactile feedback also has potential in applications during physical exercise. The potential use of vibrotactile feedback can be in cycling for, among other, correcting the aerodynamic position. Applications in other sports and health-related domains are feasible as well.